2021
DOI: 10.1039/d1ra01197a
|View full text |Cite
|
Sign up to set email alerts
|

All carbon hybrid N-doped carbon dots/carbon nanotube structures as an efficient catalyst for the oxygen reduction reaction

Abstract: The ORR measurements showed that the CD(ED)/CNT catalyst was superior to CD(EG)/CNT and CD(EA)/CNT. They even surpassed the activity of commercial Pt/C in terms of durability, Tafel slope, and MeOH tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Nguyen and Shim designed and synthesized an N‐doped carbon quantum dots/multiwalled carbon nanotubes (CDs/CNTs) hybrid by a facile and scalable synthesis method. [ 275 ] The obtained CDs/CNT exhibited excellent ORR activity ( E 1/2 = 0.834 V vs RHE) with favorable kinetics, as well as high durability ascribed to the synergistic effect of CDs and CNTs. Shui et al.…”
Section: N‐doped Carbon Catalysts For Oxygen Electrocatalysismentioning
confidence: 99%
“…Nguyen and Shim designed and synthesized an N‐doped carbon quantum dots/multiwalled carbon nanotubes (CDs/CNTs) hybrid by a facile and scalable synthesis method. [ 275 ] The obtained CDs/CNT exhibited excellent ORR activity ( E 1/2 = 0.834 V vs RHE) with favorable kinetics, as well as high durability ascribed to the synergistic effect of CDs and CNTs. Shui et al.…”
Section: N‐doped Carbon Catalysts For Oxygen Electrocatalysismentioning
confidence: 99%
“…Defective oxygen-containing moieties were randomly distributed in the basal plane and edge sites. 60 Wang et al effectively combined the graphene oxide quantum dots (GOQDs) into graphene/carbon nanotube (CNT) hybrid structures using GOQDs-dispersed solution. 69 GOQDs with abundant oxygen containing functional groups and unsaturated bonds provided nitrogen and sulfur doping sites, which increased the doping level of electrocatalysts.…”
Section: Design Of Electrocatalysts For Zabsmentioning
confidence: 99%
“…[57][58][59] In addition, it has emerged as a promising electrocatalyst owing to its advantages such as earth abundance, low price, environmental friendliness, and ease in tunability of their catalytic properties and structures. 60,61 Heteroatom doping strategies have been widely studied as an efficient way to improve the catalytic properties of metal-free carbon-based electrocatalysts. 56,57,[62][63][64] Many studies demonstrated that heteroatom doping can change the sp 2 electronic structures of carbon materials and electrocatalytically active sites could be formed between elements with a different electronegativity.…”
Section: Metal-free Electrocatalystsmentioning
confidence: 99%
“…CDs have positively inferior oxygen-possessed moieties dispersed unsystematically on the basal plane and border areas. [104] Current research indicates that N-doped CNMs appear to be an exemplary process for promoting ORR. For example, Qu et al [105] prepared N-doped GQDs (N-GQDs) through CV cycles.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
“…CDs have positively inferior oxygen‐possessed moieties dispersed unsystematically on the basal plane and border areas. [ 104 ]…”
Section: Electrochemical Energy Storage Applications Toward Environme...mentioning
confidence: 99%